1985
DOI: 10.1111/j.1432-1033.1985.tb09133.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible dissociation of aspartokinase I/homoserine dehydrogenase I from Escherichia coli K 12. The active species is the tetramer

Abstract: Dimers of aspartokinase I/homoserine dehydrogenase 1 from Escherichiu coli K 12 have been isolated under very mild conditions. The dimers which cannot be distinguished from the tetramers by their kinetic properties, reassociate in the presence of potassium ions or L-aspartate. The selective sensitivity of aspartokinase I/homoserine dehydrogenase I to mild proteolytic digestion of dimers has been used to probe the reassociation reaction under the conditions of aspartokinase assay. We demonstrate that rapid reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Carrot AK was also shown to dissociate into independently migrating active species of 100,000 and 150,000 during sucrose density gradient centrifugation (21). Escherichia coli aspartokinase I/homoserine dehydrogenase I also exists in different active aggregation states, a 320,000 tetramer and a 122,000 dimer (25,26 The two subunits resolved from AK Late may be products of two genes or result from in vitro or in vivo modification of a single gene product. At least two genes encode different barley AK isozymes (22); however, barley AK isozymes have not been characterized at the structural level to determine subunit composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrot AK was also shown to dissociate into independently migrating active species of 100,000 and 150,000 during sucrose density gradient centrifugation (21). Escherichia coli aspartokinase I/homoserine dehydrogenase I also exists in different active aggregation states, a 320,000 tetramer and a 122,000 dimer (25,26 The two subunits resolved from AK Late may be products of two genes or result from in vitro or in vivo modification of a single gene product. At least two genes encode different barley AK isozymes (22); however, barley AK isozymes have not been characterized at the structural level to determine subunit composition.…”
Section: Discussionmentioning
confidence: 99%
“…The gel filtration column was eluted at 20 mL/h overnight. Fractions containing AK activity were pooled and diluted with one volume of AE1 buffer (25 [v/ v] glycerol, 3 mm DTT). The enzyme was loaded at this higher pH onto the Mono Q HR5/5 column and eluted with a 30-mL KCI gradient (0-500 mM) into 0.5 mL fractions.…”
Section: Aspartate Kinase Activity Coupled Assaymentioning
confidence: 99%
“…The biochemistry of AKs in bacteria and plants is quite complex. The AKs from Escherichia coli include the bifunctional AK-HDH I which assembles into a 360 kDa tetrameric complex (Veron et al, 1985), while the second bifunctional enzyme (AK-HDH II) is found as a dimer in solution (Dautry-Varsat et al, 1977). The monofunctional AK III from E. coli assembles into a smaller dimer of only 96 kDa (Richaud et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The recent report that aspartokinase 1/homoserine dehydrogenase I in the dimeric form was subject to inactivation by pronase type VI, while conversion to the tetramer rendered it much more resistant to cleavage of the protein molecule (13) suggests other mechanisms by which enzymes may be regulated, ' Supported in part by grant DMB 85-15181 from the National Science Foundation.…”
mentioning
confidence: 99%